2020
DOI: 10.1182/blood.2019002165
|View full text |Cite
|
Sign up to set email alerts
|

Wdr26 regulates nuclear condensation in developing erythroblasts

Abstract: Mammalian red blood cells lack nuclei. The molecular mechanisms underlying erythroblast nuclear condensation and enucleation, however, remain poorly understood. Here we show that Wdr26, a gene upregulated during terminal erythropoiesis, plays an essential role in regulating nuclear condensation in differentiating erythroblasts. Loss of Wdr26 induces anemia in zebrafish and enucleation defects in mouse erythroblasts because of impaired erythroblast nuclear condensation. As part of the glucose-induced degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…In particular, the different Gid7 orthologs form distinct supramolecular assemblies ( Figure 6 ). We speculate that the unique assemblies define distinct functions, as implied by varying phenotypic alterations upon their individual mutation ( Bauer et al., 2018 ; Nassan et al., 2017 ; Skraban et al., 2017 ; Zhen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the different Gid7 orthologs form distinct supramolecular assemblies ( Figure 6 ). We speculate that the unique assemblies define distinct functions, as implied by varying phenotypic alterations upon their individual mutation ( Bauer et al., 2018 ; Nassan et al., 2017 ; Skraban et al., 2017 ; Zhen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhen and colleagues reported that during terminal erythropoiesis, which is characterized by erythroblast nuclear condensation and enucleation, Wdr26, a core component of the CTLH E3 ubiquitin ligase complex, targets several nuclear proteins, including B-lamins, for ubiquitination and proteasomal degradation [ 73 ]. Interestingly, the expression levels of lamin A/C were mostly unaffected by Wdr26 or by depletion of Rmnd5a, another core component of the CTLH E3 ligase complex which cooperates with Wdr26 in the regulation of B-lamins.…”
Section: Regulation Of Nls By the Ubiquitin And Atg8-atg12 Conjugamentioning
confidence: 99%
“…Physiological importance of the CTLH E3 is underscored by developmental defects in flies, fish, frogs, and mammals arising from genetic deletions or mutations of its subunits (Han et al, 2016;Javan et al, 2018;Nguyen et al, 2017;Pfirrmann et al, 2015;Soni et al, 2006;Wei et al, 2019;Zavortink et al, 2020;Zhen et al, 2020). Yet, how Gid7 or its human orthologs regulate GID and CTLH E3 ligase complexes is unknown.…”
Section: Introductionmentioning
confidence: 99%